Shaping multilateral regional governance of climate and forests: Exploring the influence of Forest industry lobbying on state participation - Polo-Villanueva, Fredy David; Bulian, Simon; Rivadeneira, Laura; Tosun, Jale; Gießen, Lukas; Burns, Sarah Lilian (Forest policy and economics, 2024)
This study aims to characterise the institutional dynamics of Multilateral Regional Governance Arrangements at the Climate-Forest Interface (MRGA-CFI) and investigate the influence of the forest industry lobby groups on state participation in these arrangements. We use an original dataset to characterise the issue scope, spatial ambit, and governance functions of MRGA-CFI. State participation in these arrangements is modelled as a function of the strength of the forest industry lobby groups; measured as the proportion of forest that has been planted in a state, alongside various control variables. Our findings reveal that most MRGA-CFI focus on forests but are relevant for climate issues, have contiguous spatial ambit primarily in Asia and Africa, and focus on knowledge dissemination and capacity building. Quantitative analysis reveals a positive significant association between the strength of the forest industry lobby groups and state participation in MRGA-CFI. The analysis further suggests that states with stronger forest industry lobby groups are more likely to participate in non-centralised arrangements and those that focus on forest but not climate. Conversely, such states are also less likely to participate in governance arrangements that focus on both forest and climate issues. We conclude that while regional cooperation on climate and forests has been designed to capture funds from the climate regime and form negotiating coalitions, the forest industry lobbies governments to prevent such cooperation from overregulating their economic activities.